2019
DOI: 10.1108/mi.2019.8116
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body mass and clinical response to repetitive transcranial magnetic stimulation (rTMS) for major depressive disorder

Abstract: Repetitive transcranial magnetic stimulation (rTMS) has been proven to be efficacious in the treatment of Major Depressive Disorder (MDD). We previously examined the effectiveness of rTMS for MDD in an applied clinical setting, AwakeningsKC Clinical Neuroscience Institute (CNI) and found high remission rates for patients diagnosed with MDD following rTMS treatment. An unexpected relationship with body composition and rTMS unit was discovered. This sub-study extends the previous investigation through a focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…7 The study was conducted at AwakeningsKC Clinical Neuroscience Institute (CNI), a suburban tertiary psychiatric clinic, using PHQ-9 scores and Cox Proportional Hazard and Log-Rank statistics to compare the remission rates of depression between the two machines. This study, the second of a series of three, [8][9] found that patients treated using the MagVenture instrument experienced a shorter mean time to remission, higher overall 6-week remission rates, and augmented response rates to CBT. These conclusions raise the question: Are rTMS machines equivalent, and if not, which device should be the standard of care?…”
mentioning
confidence: 69%
“…7 The study was conducted at AwakeningsKC Clinical Neuroscience Institute (CNI), a suburban tertiary psychiatric clinic, using PHQ-9 scores and Cox Proportional Hazard and Log-Rank statistics to compare the remission rates of depression between the two machines. This study, the second of a series of three, [8][9] found that patients treated using the MagVenture instrument experienced a shorter mean time to remission, higher overall 6-week remission rates, and augmented response rates to CBT. These conclusions raise the question: Are rTMS machines equivalent, and if not, which device should be the standard of care?…”
mentioning
confidence: 69%
“…Regarding BMI, a study has reported that remission rates of people with obesity (BMI ≥ 30) are greater than those without obesity. Plus, obese depressed people show a shorter time to remission 34 …”
Section: Discussionmentioning
confidence: 99%